Low-output-impedance electronically adjustable universal filter using voltage differencing buffered amplifiers - Pimpol, Jirapun; Roongmuanpha, Natchanai; Tangsrirat, Worapong (My University, 2019)
In this study, a voltage-mode universal filter with three inputs and single output is presented. The circuit is resistor-less, and consists of only two VDBAs and two capacitors. The proposed TISO filter realizes all the five standard biquadratic filter functions at the low-impedance-output terminal without any component matching criterion. The effect of the VDBA non-idealities on the presented filter performance is also discussed in detail. To prove the theoretical finding, simulation results are provided using PSPICE software.
Keywords: Electronically adjustable; Low-impedance output terminal; Universal filter; Voltage Differencing Buffered Amplifier (VDBA); Voltage-mode circuit